The next tick on Nasdaq: Does level II information matter? - Bruce Mizrach (Rutgers University, Department of Economics, 2002)
The Nasdaq stock market provides information about buying and selling interest in what is called the Level II display. Using a bivariate VAR model of trades and quotes, I assess the effect of Level II prices and depths on short-run quote dynamics. I also determine the influence of individual market makers and electronic networks and find evidence of strategic behavior. Finally, I produce a set of dynamic market price responses to buy and sell orders, and I find that these estimates vary with standard measures of liquidity.
Keywords: G14; 330; Level II; microstructure; Nasdaq; tick; Aktienmarkt; Schätzung; USA; Neuer Markt; Börsennotierung